End of life care for older adults in the criminal justice system: a brief report from a nominal group - Heathcote, Leanne (The journal of forensic psychiatry & psychology, 2025)
As a result of the ageing prison population, it is anticipated that there will be a steady increase in individuals living in prison requiring access to End of Life (EoL) care in coming years. Research in this area is limited, despite it being concern of policy makers for several years. This paper aims to explore current EoL care provision in prison via nominal group methodology, to identify what forms of care have been implemented, what provision needs to be developed, and how might this be achieved. Ten professionals were recruited to a nominal group discussion and four themes were identified: 1) ‘Consistent Family Input’; 2) ‘Staffing’; 3) ‘Ensuring Best Practice’; and 4) ‘Person-Centred Assessment’. There was consensus that care pathways are currently in place for older prisoners diagnosed with a life limiting disease; however, the consistency of services is variable. Policy makers should consider the development of a national prison EoL strategy which embeds current good areas of practice whilst promoting equitable care delivery using multi-agency networks across the prison estate.